Answer:
x = 45, y = 5
Step-by-step explanation:
It is given that two lines form a linear pair with equal measures. Therefore, the angle between the two lines will be 90. Now, according to the question,
2x + 20y - 10 =90
2x+20y = 100
x + 10y = 50
And
2x = 20y-10
x = 10y -5
x - 10 y = -5
Now, adding x + 10y = 50 and x - 10y =-5, the value of x can be found. The required value will be:
x + 10y =50
x - 10y = -5
------------------
x = 45
Therefore, the value of y after substitution of the value of x in one of the equations will be:
90 = 20y - 10
20 y = 100
y = 5
Hence, the required value of x and y are 45 and 5 respectively.
By definition of circumference, the length of the arc EF (radius: 6 in, central angle: 308°) shown in red is approximately equal to 32.254 inches.
<h3>How to calculate the length of an arc</h3>
The figure presents a circle, the arc of a circle (s), in inches, is equal to the product of the <em>central</em> angle (θ), in radians, and the radius (r), in inches. Please notice that a complete circle has a central angle of 360°.
If we know that θ = 52π/180 and r = 6 inches, then the length of the arc CD is:
s = [(360π/180) - (52π/180)] · (6 in)
s ≈ 32.254 in
By definition of circumference, the length of the arc EF (radius: 6 in, central angle: 308°) shown in red is approximately equal to 32.254 inches.
<h3>Remark</h3>
The statement has typing mistakes, correct form is shown below:
<em>Find the length of the arc EF shown in red below. Show all the work.</em>
To learn more on arcs: brainly.com/question/16765779
#SPJ1
9+12>18
12+18>9
9+18>12
So, yes. A triangle can be formed by the given angles.
Answer:
x=-7
Step-by-step explanation:
Simplifying
3(x + -2) = 5x + 8
Reorder the terms:
3(-2 + x) = 5x + 8
(-2 * 3 + x * 3) = 5x + 8
(-6 + 3x) = 5x + 8
Reorder the terms:
-6 + 3x = 8 + 5x
Solving
-6 + 3x = 8 + 5x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-5x' to each side of the equation.
-6 + 3x + -5x = 8 + 5x + -5x
Combine like terms: 3x + -5x = -2x
-6 + -2x = 8 + 5x + -5x
Combine like terms: 5x + -5x = 0
-6 + -2x = 8 + 0
-6 + -2x = 8
Add '6' to each side of the equation.
-6 + 6 + -2x = 8 + 6
Combine like terms: -6 + 6 = 0
0 + -2x = 8 + 6
-2x = 8 + 6
Combine like terms: 8 + 6 = 14
-2x = 14
Divide each side by '-2'.
x = -7
Simplifying
x = -7